A Meta-Analysis of the Structural Validity of Original and Brief Versions of the Personality Inventory for DSM-5 in Iran - Saeid Komasi; Andre Kerber; Christopher James Hopwood (Iranian Journal of Psychiatry)
Objective: The Personality Inventory for DSM-5 (PID-5) is a widely used scale to evaluate the dimensional constructs of two trait models proposed by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and the International Classification of Diseases (ICD-11). The present meta-analysis first aimed to examine the factor structure, reliability, and congruence coefficients of the Persian version of the PID-5 to assess both trait models. The second aim was to evaluate the factor structure and reliability of the Persian version of the Personality Inventory for DSM-5-Brief Form (PID-5-BF). Method: A systematic search was conducted in PubMed, Magiran, and SID to find records in English and Farsi from January 2013 to December 2023. According to the PRISMA, data from nine medium- to high-quality reports including 7,608 participants were analyzed using the random-effects method. Quality of studies, heterogeneity, and publication bias were reported. Results: The five-factor structure of the PID-5 to measure both trait models was supported by the pooled estimates of factor loadings. The alpha coefficient median for the DSM-5 model was 0.83 (range: 0.82-0.90), and the congruence coefficient median was .91 (range: 0.80-0.97). The ICD-11 alpha median was .78 (range: 0.68-0.91), and congruency median was 0.90 (range: 0.71-0.96). The factor loadings for negative affectivity, detachment, antagonism, disinhibition, and psychoticism on the PID-5-BF were 0.44-0.69, 0.38-0.67, 0.46-0.72, 0.42-0.70, and 0.44-0.76, respectively, and the alpha median was 0.73 (range: 0.65-0.76). Conclusion: Since both the original and brief versions of the PID-5 are valid and strongly similar to international structures, the clinical and research applications of these questionnaires are recommended to mental health professionals in Iran.